Mierniki wartości przedsiębiorstwa w badaniu kondycji finansowej przedsiębiorstwa - Kowalak, Robert (Measures of Value in Financial Analysis of Companies, 2005)
This article presents the possibility of using value measure in financial analysis of companies. They can replenish they the scale of financial ratios in marking opinion about profitability and market value of enterprise. Advantage is so, that they use corrected book value asset equity and liabilities presented in finance statement. In article presented three chosen measure: EVA, MVA and SVA.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1073, s. 40-46